PENGARUH MEDIA FILM ANIMASI TERHADAP MOTIVASI BELAJAR IPS SISWA SDN 002 SAMARINDA KOTA - Muhammad Fadlang; Yahya Anugrah; Ririn Alpriani (STKIP Subang, 2025)
This study aims to determine the effect of animated film media on students’ learning motivation in Social Studies at SDN 002 Samarinda Kota. The research employed a pre-experimental design with a one-group pretest–posttest model. The sample consisted of 39 students selected using a saturated sampling technique. Data collection was carried out through motivation questionnaires given before and after the treatment using animated film media in Social Studies learning. The results of statistical analysis using SPSS version 22 showed that students’ motivation increased significantly after the implementation of the animated film media. The average score of students’ motivation improved from the pretest result of 99.95 to the posttest result of 125.18. Furthermore, the paired sample t-test analysis revealed a significance value of 0.000 (p < 0.05), indicating that there was a significant difference in students’ motivation before and after the treatment. These findings suggest that animated film media can serve as an effective instructional medium to enhance students’ learning motivation and engagement in Social Studies learning. Therefore, animated film media can be recommended as an innovative alternative to improve the quality of Social Studies instructional processes in elementary schools.